2022
DOI: 10.2147/jmdh.s363421
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Handgrip Strength Among Older Adults in Malaysia

Abstract: Purpose Handgrip strength (HGS) is indicative of overall physical health among older adults. A decrease in HGS may be associated with an increased risk of disease. The aim of this study is to determine the factors associated with HGS among older adults in Malaysia. Patients and Methods One thousand two hundred four (1204) participants from urban and rural areas in Selangor state, Malaysia, were recruited. Sociodemographic and health-related conditions were gathered thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Our findings of low HGS to be associated with increased risk of NCD are in line with previous reports reporting low HGS to be associated with increased risk of cardiovascular disease (Leong et al 2015), cardiometabolic disorders (CMD) (Hao et al 2020) and the metabolic syndrome (Sayer et al 2007). Furthermore, a recent study of older adults in Malaysia found low HGS to be associated with increased prevalence of diabetes and hypertension (Shah et al 2022). In our study, NCD and osteoarthritis had higher impact on men's HGS and less so among women.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings of low HGS to be associated with increased risk of NCD are in line with previous reports reporting low HGS to be associated with increased risk of cardiovascular disease (Leong et al 2015), cardiometabolic disorders (CMD) (Hao et al 2020) and the metabolic syndrome (Sayer et al 2007). Furthermore, a recent study of older adults in Malaysia found low HGS to be associated with increased prevalence of diabetes and hypertension (Shah et al 2022). In our study, NCD and osteoarthritis had higher impact on men's HGS and less so among women.…”
Section: Discussionsupporting
confidence: 91%
“…(11) Association of age and HGS of dominant and non-dominant hand had also been evaluated in this study. The outcome of the current study revealed that age and HGS were also significantly correlated in a negative manner, confirming the previous studies done by Shamsul Azhar Shah, et all (21), Agnieszka Wiśniowska-Szurlej, et all (23), Hirokazu Inoue, et all (31) and Xuemei Lu, et all (32) that revealed strong, negative and statistically significant relation between age and HGS. On the other hand, current study's result about age was contrary to the previous study conducted by Luigi Barrea, et all that showed no evident correlation between HGS and age.…”
Section: Discussionsupporting
confidence: 90%
“…The association between body mass index and handgrip strength has been widely established. Some studies revealed positive association between HGS and BMI as Shamsul Azhar Shah, et all revealed through their study (21) but some of them showed negative relation between them as Dhananjaya J R, et all (10) and Luigi Barrea, et all showed through their study. (22) Furthermore, in some studies, it is shown that BMI and HGS has no significant relationship.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, Kawamoto et al 69 reported that grip strength increased with higher daily alcohol consumption in Japanese adults. Shan et al 70 observed a positive relationship between alcohol intake and handgrip strength in Malaysians, although the drinking group in that study were younger than the abstaining group. Additionally, Molina-Hidalgo et al 71 found that short-term daily alcohol consumption did not impact physical performance in healthy young adults.…”
Section: Discussionmentioning
confidence: 69%